Agricultural land and crop production in Myanmar - Lambrecht, Isabel B.; Belton, Ben; Fang, Peixun; Minten, Bart; Naing, Phyo Thandar (International Food Policy Research Institute, 2022)
Southeast Asia’s agricultural landscape is known for rice production in lowland areas, diverse upland areas, and the cultivation of ‘boom crops’ in the borderlands. Despite general similarities across different Southeast Asian countries, each has its own distinct history and patterns of land use, access, and ownership. However, little is documented, particularly for Myanmar, the second largest country in Southeast Asia. We therefore focus on agricultural land ownership and use patterns in Myanmar and employ nationally representative household survey data to document patterns at the national level and by agro-ecological zone. We explore inequality in landholdings, land tenure arrangements and documents, cropping patterns, and irrigation access.